SPECIFIC CHARACTERISTICS OF TODAY'S UZBEK NOVEL AND FORMAL RESEARCH (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2023)
It is known that many studies have been made about the nature of the novel genre. There is no special pattern in the novel, it is not proven that there is a law of universality and repetition. The theoretical principle of the novel is constant search and renewal. The first novels originated among the Romani-speaking peoples. It corresponds to the 12th - 13th centuries AD. Romance language speakers include Spanish, Italian, Moldovan, Portuguese, Romanian, French.